Predicting the acoustic characteristics of seafloor sediments containing cold spring carbonate rocks - Tian, Yuhang; Wu, Lei; Zou, Dapeng; Chen, Zhong; Jiang, Yongjun; Yan, Pin; Fan, Chaoyan (Frontiers in Marine Science, 2023)
The acoustic and physical properties of two valuable marine cold spring carbonate rock samples gathered from the Chaoshan Depression in the South China Sea were measured. The Wyllie time-average equation was applied to analyze the measured sound speeds and their trend under different porosities, and the sound speeds of marine cold spring carbonate rocks were found to be consistent with those of terrestrial carbonate rocks. The Voigt model, Reuss model, and Voigt-Reuss-Hill model were used to predict the characteristics of the sound speed for four states of seafloor sediments containing cold spring carbonate mineral particles or rocks. For these four states of marine cold spring carbonate mineral particles existing on or in seafloor sediments, the sound speed and reflection coefficient of a mixture of seafloor surface sediments containing cold spring carbonate mineral particles or rocks decrease with an increase in the volume ratio of the seafloor sediment. This method for predicting the reflection coefficient provides evidence to explain the high and low reflection coefficients observed in Chirp sub-bottom profiles of cold spring seepage areas.